Pathologic lesions in children with acquired immunodeficiency syndrome an autopsy study of 11 cases from Mumbai, India - Dhanesheshwar N Lanjewar; Varsha Omprakash Bhatia; Sonali Dhaneshwar Lanjewar (Wolters Kluwer Medknow Publications, 2016)
Background: Human immunodeficiency virus (HIV) infection in India has now been prevalent over three decades, and an increasing number of children are being affected with HIV. The spectrum of pathologic lesions in children with acquired immunodeficiency syndrome (AIDS) in India has not been well described. Materials and Methods: A review of systematically conducted autopsies of 11 (10 boys and 1 girl) children with AIDS is presented. Results: The mode of HIV transmission in 6 children was vertical; in one it was blood transfusion and in 4 children route was presumably vertical as these were children of orphanage. The clinical manifestations were failure to thrive; 9 children, persistent gastroenteritis; 8, recurrent fever; 5, bacterial infections; 5, hepatosplenomegaly; 5, candidiasis; 1, scabies; 1, skin rash; 2, tuberculous (TB) meningitis; 1 and paraplegia; in 1 child. The spectrum of pathologic lesions observed were precocious involution in thymus in 3 and dysinvolution in 2 cases. Infectious diseases comprised of TB; 4 cases, cytomegalovirus infection (CMV) 4; bacterial pneumonia and meningitis; 7, and esophageal candidiasis in 2 cases. Dual or multiple infections were observed in 9 (82%) cases; these comprised of two lesions in 2, three lesions in 2, four lesions in 4, and five lesions in 1 case. TB, bacterial pneumonia, meningitis, and CMV infection are the most frequent causes of death in children with AIDS. Vascular lesions showing features of arteriopathy were observed in 5 cases and brain in one case showed non-Hodgkin's lymphoma. Conclusions: This study provides a better insight into the spectrum of pathologic lesions in children with AIDS in India. TB and CMV infection has been found to be the most prevalent infection in our children.